Liquidity Determinants of the Selected Banking Sectors and their Size Groups - Jana Laštůvková (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2016)
The article focuses on the factors affecting the liquidity of selected bank sectors, as well as their size groups, using panel regression analysis. For higher complexity of the results, multiple dependent variables are used: liquidity creation, outflow and net change. The values are calculated based on the specific method of liquidity risk measurement – gross liquidity flows. The results indicate both multiple effects of some factors on the given variables, as well as isolated influence of factors on a single liquidity form or size group. Thus, when looking for determinants using just one form of liquidity, such as creation, the results need not necessarily comprehensively show the influence of the given factors, and can lead to erroneous conclusions. The results also point to the differing behaviours of the size groups and their different sensitivity on the factors; smaller banks have shown higher sensitivity on macroeconomic variables. Higher flexibility in regulation could lead to higher optimization.